Methods in Latin Computational Linguistics. - McGillivray, Barbara (Brill's studies in historical linguistics., 2013)
In Methods in Latin Computational Linguistics, Barbara McGillivray presents some of the methodological foundations of Latin Computational Linguistics through three corpus case studies covering morpho-syntactic and lexical-semantic aspects of Latin verb valency and quantitative diachronic explorations of Latin prefixed verbs.